Cigarette Smoking Quit Rates Among Persons With Serious Psychological Distress in the United States From 2008 to 2016: Are Mental Health Disparities in Cigarette Use Increasing?. Issue 1 (23rd October 2018) - Streck, Joanna M; Weinberger, Andrea H; Pacek, Lauren R; Gbedemah, Misato; Goodwin, Renee D
Abstract: Introduction: Prior work suggests that the prevalence of cigarette smoking is persistently higher among people with mental health problems, relative to those without. Lower quit rates are one factor that could contribute to higher prevalence of smoking in this group. This study estimated trends in the cigarette quit rates among people with and without past-month serious psychological distress (SPD) from 2008 to 2016 in the United States. Methods: Data were drawn from 91 739 adult participants in the 2008–2016 National Survey on Drug Use and Health, a repeated, cross-sectional, national survey. Linear time trends of cigarette quit rates, stratified by past-month SPD, were assessed using logistic regression models with continuous year as the predictor. Results: Cigarette quit rates among individuals with past-month SPD were lower than among those without SPD every year from 2008 to 2016. Quit rates did not change appreciably among those with past-month SPD (odds ratio = 1.02 [0.99, 1.06]) from 2008 to 2016, whereas quit rates increased among those without past-month SPD (odds ratio = 1.02 [1.01, 1.02]). Conclusions: In the United States, quit rates among individuals with past-month SPD are approximately half than quit rates of those without SPD and have not increased over the past decade. This discrepancy in quit rates may be one factor driving increasing disparities in prevalence of smoking among those with versus without mental health problems. Tobacco control efforts require effective and targeted interventions for those with mental health problems. Implications: Cigarette smoking quit rates have not increased among persons with serious mental health problems over the past decade. This work extends prior findings showing that smoking prevalence is not declining as quickly among persons with serious mental health problems. Findings suggest that diverging trends in quit rates are one possible driver of the persistent disparity in smoking by mental health status. Innovation in both tobacco control and targeted interventions for smokers with mental health problems is urgently needed.